Um estudo sobre as demandas judiciais dos avós nas varas de família - Rocha, Sandra Monica de Siqueira (2017)
The demographic changes, among which stand out the greater human longevity and declining birth rates, have contributed to a major role of grandparents within the family and society. In addition, factors such as the insertion of women in the labor market, socioeconomic difficulties, adolescent pregnancy, divorce rate and remarriage, have required a constant presence of the grandparents with the grandchildren, temporarily or permanently. Accompanying these changes, one notices an increasing demand of the grandparents to Justice, often to regularize an already established situation in the family. In judicial framework appears the formulation of new laws reflecting the necessities that correspond to the specificities of the relations in the present family. The purpose of this paper is to understand the reasons that are leading the grandparents to justice based on the psychosocial reports that subsidize judicial decisions on family issues. This is a documentary research, of character qualitative which was based on the analysis of these reports, which was researched at the Centro de Apoio Psicossocial (Center of Psychosocial Support of the Court of Justice of Pernambuco), referring to the period of January 2010 to December 2014. The reports were identified from lawsuits brought by grandparents, and analyzed their motivations from the point of view of professional psychologists and social when drawing up reporting. Initially, a sociodemographic survey was carried out, where we could observe common characteristics between the judicial actions analyzed and subsequently describe the most frequent arguments used by the grandparents. Based on the results, there was a significant participation of grandparents in these legal custody proceedings, since they were the main guardians of their grandchildren, sometimes by the absence of parents, or by their disability. It stood out almost all cases the search for emotional and financial support to support the creation of grandchildren, among which was observed a high rate of applications for Judicial Guard by the grandparents. It is hoped to contribute to give visibility to the demand of grandparents within the Justice, verifying their participation especially in times of family crisis, especially in cases of divorce or separation of the parents of the grandchild, a dispute over the custody of grandchildren and alimony.